Synthesis, crystal structure, photophysical properties, DFT studies and Hirshfeld surface analysis of a phosphorescent 1, 2, 4-triazole-based iridium(III) complex. (15th September 2020) - Bain, Nurul Husna As Saedah; Ali, Noorshida Mohd; Juahir, Yusnita; Hashim, Norhayati; Isa, Illyas Md; Mohamed, Azmi; Kamari, Azlan; Anouar, El Hassane; Yamin, Bohari Mohd; Tajuddin, Amalina Mohd; Baharudin, Muhammad Hazim
Graphical abstract: In this work, the synthesis, spectroscopic characterization and crystal structure of the [Ir(2, 4-F2 ppy)2 (pyta)Cl] complex are presented. Remarkably, this Ir(III) complex exhibits a blue-green emission (λem  = 469 nm) at room temperature. TD-DFT calculations have been performed to derive a simulated absorption spectrum and vertical excitation energies. Highlights: Our group is focusing on a synthesized [Ir(2, 4=F2 ppy)2 (pyta)Cl] complex. Characterization of the Ir(III) complex was done by NMR, FTIR, UV–Vis and LC-QTOF/MS. Molecular structure of Ir(III) complex was determined by single crystal XRD technique. Photophysical studies and DFT calculations on Ir(III) complex have been performed. Abstract: The cyclometallated Ir(III) complex [Ir(2, 4-F2 ppy)2 (pyta)Cl], where ppy and pyta denote 2-phenylpyridine and pyridine-triazole respectively, was successfully synthesized by the reflux reaction of the 2-(1H-1, 2, 4-triazol-1-yl)pyridine ligand with the Ir(III) dimer [Ir(2, 4-F2 ppy)2 (µ-Cl)]2 . The Ir(III) complex were characterized by spectroscopic methods: NMR, FTIR, UV–Vis and LC-QTOF/MS, while the molecular structure was determined by the single crystal X-ray diffraction technique. The X-ray crystallographic study revealed that the Ir(III) ion was coordinated to one pyridine-triazole, one chloro and two difluorophenylpyridine ligands in a distorted octahedral geometry. Steady-state emission spectroscopy demonstrated that the Ir(III) complex emitted blue-green light in dichloromethane solution with an emission maximum at 469 nm due to the admixtures of 3 LC and 3 MLCT character excited states. DFT calculations on the Ir(III) complex showed that the HOMO was localized predominantly over the cyclometallating ligands and the Ir 5 d orbitals, whilst the LUMO was located on both cyclometallating ligands, with the HOMO-LUMO energy gap being 3.86 eV. The intercontacts between different units of the cyclometallated Ir(III) complex were investigated by analyzing the Hirshfeld surface and molecular electrostatic potential surface plotted in the ground and triplet excited states. The X-ray structure of the Ir(III) complex was relatively well reproduced with B3LYP/LANL2DZ level of theory, where the two structures, experimental and theoretical, were well superposed. The calculated ground and triplet excited states geometries showed slight differences.